Defining El Niño indices in a warming climate. (11th March 2021) - van Oldenborgh, Geert Jan; Hendon, Harry; Stockdale, Timothy; L'Heureux, Michelle; Coughlan de Perez, Erin; Singh, Roop; van Aalst, Maarten
Abstract: Extreme weather and climate events associated with El Niño and La Niña cause massive societal impacts. Therefore, observations and forecasts are used around the world to prepare for such events. However, global warming has caused warm El Niño events to seem bigger than they are, while cold La Niña events seem smaller, in the commonly used Niño3.4 index (sea surface temperature (SST) anomalies over 5 ∘ S–5 ∘ N, 120–170 ∘ W). We propose a simple and elegant adjustment, defining a relative Niño3.4 index as the difference between the original SST anomaly and the anomaly over all tropical oceans (20 ∘ S–20 ∘ N). This relative index describes the onset of convection better, is not contaminated by global warming and can be monitored and forecast in real-time. We show that the relative Niño3.4 index is better in line with effects on rainfall and would be more useful for preparedness for El Niño and La Niña in a changing climate and for El Niño—Southern Oscillation research.